2022
DOI: 10.3389/fpsyg.2022.857878
|View full text |Cite
|
Sign up to set email alerts
|

The reciprocal relationships between Chinese children’s perception of interparental conflict, negative thinking, and depression symptoms: A cross-lagged study

Abstract: The present longitudinal study used the traditional cross-lagged panel model (CLPM) and autoregressive latent trajectory model with structured residuals (ALT-SR) to examine the relationships between perceived interparental conflict (IPC), negative thinking (NT), and depression symptoms in Chinese children. Changes in these three variables over time were also examined, as well as the trait and state aspects of the relationships between them. A sample of 516 third-grade primary students completed questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…This result was in line with previous studies ( Bai et al, 2022 ; Jekielek, 1998 ; Zhen et al, 2022 ). For instance, a study of 516 primary school students found that interparental conflict was significantly positively associated with the level of children's depressive symptoms ( Yang et al, 2022 ). In fact, some researchers have pointed out that conflicts between parents exert an adverse impact on children's development and might result in externalizing or internalizing behavior problems ( Rhoades, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was in line with previous studies ( Bai et al, 2022 ; Jekielek, 1998 ; Zhen et al, 2022 ). For instance, a study of 516 primary school students found that interparental conflict was significantly positively associated with the level of children's depressive symptoms ( Yang et al, 2022 ). In fact, some researchers have pointed out that conflicts between parents exert an adverse impact on children's development and might result in externalizing or internalizing behavior problems ( Rhoades, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, future studies can adopt multi-dimensional scales ( Grych et al, 2010 ; Straus et al, 1998 ) to comprehensively evaluate interparental conflict and parent–child conflict. Second, although most studies acknowledged that verbal antagonism was the most important dimension of conflict within a family ( Grych et al, 1992 ; Yang et al, 2022 ), some relevant studies operationalized interparental conflict and parent–child conflict as negative verbal interactions such as nagging and quarreling ( Leung, 2020 ; Sherrill et al, 2017 ), while others assessed family conflict using multi-dimensional scales ( Gunlicks-Stoessel et al, 2010 ; Zhen et al, 2022 ). It is noteworthy that the difference in conceptual operationalization limited the comparisons between this study and those relevant studies.…”
Section: Discussionmentioning
confidence: 99%
“…A higher total score indicates a higher severity of depressive symptoms. Previous research has demonstrated the Chinese version of the CES-D scale's robust internal consistency and construct validity in a sizable sample of Chinese adolescents [88][89][90][91][92][93], and it has been used to assess depression in Chinese children and young adolescents [88,89,92,93]. This three-factor structure showed good model fit in various studies conducted with Chinese early adolescents [90,92].…”
Section: The Center For Epidemiological Studies Depression Scale (Ces-d)mentioning
confidence: 94%
“…The Center for Epidemiological Studies Depression (CES-D) scale was originally developed by Radloff in 1977 and has been widely used for depression measurement [87,88]. In the current study, the Chinese version of the CES-D was employed to assess depression among the participants [89][90][91].…”
Section: The Center For Epidemiological Studies Depression Scale (Ces-d)mentioning
confidence: 99%
“…Example items were as followed: (1) “I can't make myself feel better when my mom and dad fight”; (2) “My mom and dad usually still make up after every argument”. The CPIC has been validated in a Chinese context, with a Cronbach's alpha of 0.92, indicating excellent reliability ( 49 ).…”
Section: Methodsmentioning
confidence: 99%